Alteration in the Gut Microbiota of Chickens Resistant to Eimeria tenella Infection - Yu Qiao; Qian Feng; Qingjie Wang; Qiping Zhao; Shunhai Zhu; Fanghe Zhao; Zhongchuang Wang; Ruiting Zhang; Jinwen Wang; Yu Yu; Hongyu Han; Hui Dong (Microorganisms)
Avian coccidiosis, caused by several species of Eimeria, is a widespread and economically important poultry disease that inflicts severe losses in the poultry industry. Understanding the interplay between Eimeria and gut microbiota is critical for controlling coccidiosis and developing innovative treatments to ensure good poultry health. In the present study, chickens were immunized six times with a low dose of Eimeria tenella, resulting in complete immunity against Eimeria infection. The results of fecal microbiota transplantation showed that the gut microbiota of immunized chickens induced a certain degree of resistance to coccidial infection. To investigate the types of intestinal microbiota involved in the development of resistance to Eimeria, the intestinal contents and fecal samples from both immunized and unimmunized groups were collected for 16S rRNA gene sequencing. The results showed that, at the genus level, the abundance of the Eubacterium coprostanoligenes group, Erysipelatoclostridium, Shuttleworthia, and Colidextribacter was significantly increased in the intestinal content of immunized chickens, whereas the abundance of Eisenbergiella was significantly decreased. In fecal samples, the abundance of Clostridiaceae and Muribaculaceae significantly increased, whereas that of Bacillales significantly decreased. These findings will help to elucidate the interactions between E. tenella and the gut microbiota of chickens, providing a basis for isolating E. tenella-resistant strains from the gut microbiome and developing new vaccines against coccidiosis.